RANCANG BANGUN MESIN PENGUPAS BAWANG - Ningsi, Sari Widya; Wirdha, Wirdha; Kumara, Dody Candra; Gazali, Mohammad; Hair, Jumadil; Putra, Egi Kaisa (Foristek, 2024)
The making of this shallot peeling machine is intended for farmers and catering entrepreneurs to facilitate the process of peeling shallots. The research and design of this machine were conducted at the Poluteknik campus and Sirarata workshop, Sibowi Village, Tanambulava District. Sigi Regency, Central Sulawesi Province. This shallot peeling machine is very simple, using an electric motor with a speed of 1400 rpm as a driving force. This peeler rubber serves to peel the shallot skin. The result of this research is the creation of an shallot peeling machine with a frame length of 75 cm, a width of 40 cm, and a height of 88 cm so that the peeling results can help shallot farmers.